Patient attitudes to screening of alcohol consumption in primary health care (Portuguese Journal of Family Medicine and General Practice, 2012)
PATIENT ATTITUDES TO SCREENING OF ALCOHOL CONSUMPTION IN PRIMARY HEALTH CAREObjectives: To characterize the alcohol consumption of patients in Primary Health Care, to determine the attitude of patients to- wards screening for harmful alcohol consumption by their physician, to determine if these attitudes are related to the patient's AUDIT-C status, and to analyze factors (age, education, alcohol consumption) related to attitudes towards alcohol screening con- ducted by the family physician during the consultation.Study design: Analytical, cross sectionalSetting: Health Centre Groups I, III and VI of the Greater Lisbon area.Participants: Patients of both genders, aged 16 years or older.Methods: A convenience sample of 175 patients in primary health care in the Lisbon area was used. After collecting demographic information from patients, we administered a questionnaire on attitudes towards the screening of harmful alcohol consumption and the AUDIT-C instrument. The chi-square and Student t-test were used, with significance set at the 0,05 level.Results: Most patients (> 80%) expressed support for the screening of alcohol intake by their physician. The answer to four of the statements was related to age and educational level. Forty-one individuals (23.4%) with AUDIT-C positive screening were found, representing 38.5% of men and 14.5% of the women.Conclusions: Patients accept screening of alcohol consumption by their physician, independent of demographic variables or the screening method used. Patients are also open to advice regarding their alcohol intake.
Keywords: Alcoholism; Alcohol drinking; Screening; Primary health care